Peningkatan Kompetensi Profesional Dosen Menuju Kualitas Pendidikan Tingi Agama Hindu Dan Sumber Daya Manusia Hindu - I Ketut Tanu (UHN IGB Sugriwa Denpasar, 2018)
The study on increasing lecturer competence is interesting in relation to the dynamics of education and education. Especially in relation to the higher education of Hinduism is also a thing that is still rare to be observed by practitioners of Hindu religious education in particular and education globally in general. With regard to the competence of lecturers in relation to the quality of Hindu religious education the hope is for the realization of the quality of Hindu human resources. An institution of higher education can be said to have quality, depending on many factors. Many components need to be met in accordance with applicable criteria and conditions. Lately there is a tendency that learners have wisely determine which college option is chosen as a place of college. Physically, that magnificent building can be used as a measure. Then there are also choosing the completeness of facilities owned by the college. In addition, it is also seen that the graduates have the best performance in the regional and national scale. All of that is as the hope and desire of each learner to be able to follow his studies at such higher education institutions